Bisphosphonates Inhibit Pain, Bone Loss, and Inflammation in a Rat Tibia Fracture Model of Complex Regional Pain Syndrome. (October 2016) - Wang, Liping; Guo, Tian-Zhi; Wei, Tzuping; Li, Wen-Wu; Shi, Xiaoyou; Clark, J. David; Kingery, Wade S.
Abstract : BACKGROUND: Bisphosphonates are used to prevent the bone loss and fractures associated with osteoporosis, bone metastases, multiple myeloma, and osteogenesis deformans. Distal limb fractures cause regional bone loss with cutaneous inflammation and pain in the injured limb that can develop into complex regional pain syndrome (CRPS). Clinical trials have reported that antiresorptive bisphosphonates can prevent fracture-induced bone loss, inhibit serum inflammatory cytokine levels, and alleviate CRPS pain. Previously, we observed that the inhibition of inflammatory cytokines or adaptive immune responses attenuated the development of pain behavior in a rat fracture model of CRPS, and we hypothesized that bisphosphonates could prevent pain behavior, trabecular bone loss, postfracture cutaneous cytokine upregulation, and adaptive immune responses in this CRPS model. METHODS: Rats underwent tibia fracture and cast immobilization for 4 weeks and were chronically administered either subcutaneously perfused alendronate or oral zoledronate. Behavioral measurements included hindpaw von Frey allodynia, unweighting, warmth, and edema. Bone microarchitecture was measured by microcomputed tomography, and bone cellular activity was evaluated by static and dynamic histomorphometry. Spinal cord Fos immunostaining was performed, and skin cytokine (tumor necrosis factor, interleukin [IL]-1, IL-6) and nerve growth factor (NGF) levels were determined by enzyme immunoassay. Skin and sciatic nerve immunoglobulin levels were determined by enzyme immunoassay. RESULTS: Rats with tibia fractures developed hindpaw allodynia, unweighting, warmth, and edema, increased spinal Fos expression and trabecular bone loss in the lumbar vertebra and bilateral distal femurs as measured by microcomputed tomography, increased trabecular bone resorption and osteoclast surface with decreased bone formation rates, increased cutaneous inflammatory cytokine and NGF expression, and elevated immunocomplex deposition in skin and nerve. Alendronate (60 μg/kg/d subcutaneously [s.c.]) or zoledronate (3 mg/kg/d orally) treatment for 28 days, started at the time of fracture, completely inhibited the development of hindpaw allodynia and reduced hindpaw unweighting by 44% ± 13% and 58% ± 5%, respectively. Orally administered zoledronate (3 mg/kg/d for 21 days) treatment also completely reversed established allodynia and unweighting when started at 4 weeks postfracture. Histomorphometric and microcomputed tomography analysis demonstrated that both the 3 and 60 μg/kg/d alendronate treatments reversed trabecular bone loss (an 88% ± 25% and 188% ± 39% increase in the ipsilateral distal femur BV/TV, respectively) and blocked the increase in osteoclast numbers and erosion surface observed in bilateral distal femurs and in L5 vertebra of the fracture rats. Alendronate treatment inhibited fracture-induced increases in hindpaw inflammatory mediators, reducing postfracture levels of tumor necrosis factor by 43% ± 9%, IL-1 by 60% ± 9%, IL-6 by 56% ± 14%, and NGF by 37% ± 14%, but had no effect on increased spinal cord Fos expression, or skin and sciatic nerve immunocomplex deposition. CONCLUSIONS: Collectively, these results indicate that bisphosphonate therapy inhibits pain, osteoclast activation, trabecular bone loss, and cutaneous inflammation in the rat fracture model of CRPS, data supporting the hypothesis that bisphosphonate therapy can provide effective multimodal treatment for CRPS.